Predictive Factors of Radioactive Iodine Therapy Refractoriness in Patients with Differentiated Thyroid Carcinoma - Bel Lakhdar, Majdouline; Mouaden, Ayat; Zekri, Mourad; Alami, Dounia; Zarouf, Hamza; Ghfir, Imad; Guerrouj, Hasnae (World Journal of Nuclear Medicine, 2024)
Aim Differentiated thyroid carcinoma (DTC) is the most prevalent endocrine malignancy, with radioactive iodine (RAI) therapy being a standard of care. However, RAI refractoriness, occurring in a subset of patients, significantly impacts survival rates. Understanding predictive factors for RAI refractoriness is crucial for optimizing patient management.Methods This retrospective study analyzed data from 90 DTC patients at Ibn Sina University Hospital, Morocco. Patients were categorized into RAI-refractory (RAIR) and non-RAIR groups based on established criteria. Statistical analyses, including univariate and multivariate logistic regression, were performed to identify predictive factors of RAI refractoriness.Results Age at the time of diagnosis ≥ 54 years, primary tumor diameter ≥ 29 mm, and distal/nodal metastasis were independent predictors of RAIR-DTC. Additionally, the oncocytic carcinoma histological subtype significantly increased the risk of refractoriness. These findings were consistent with previous studies and underscored the importance of early detection and risk stratification.Conclusion Recognition of predictive factors for RAI refractoriness, including age, tumor size, distal/nodal metastasis, and histological subtype, facilitates early identification of high-risk patients. This enables timely intervention and personalized treatment strategies, particularly relevant in resource-limited settings. Further prospective studies are warranted to validate these findings and explore additional molecular markers for improved prediction of RAI refractoriness.
Keywords: differentiated thyroid carcinoma (DTC); radioactive iodine therapy (RAI); RAI refractoriness (RAIR); predictive factors